Internet celebrity : understanding fame online - Abidin, Crystal (Bingley, U.K. : Emerald Publishing Limited, 2018)
The face of internet celebrity is rapidly diversifying and evolving. Online and mainstream celebrity culture are now weaving together, such that breakout stars from one-hit viral videos are able to turn their transient fame into a full-time career.This book presents a framework for thinking about the different forms of internet celebrity that have emerged over the last decade, taking examples from the Global North and South, to consolidate key ideas about cultures of online fame. It discusses the overall landscape, developments and trends in the internet celebrity economy, and cross-cultural lessons.
Includes index.
Print version record
Keywords: Celebrities in mass media; Internet personalities; Fame -- Social aspects; Social Science -- Media Studies; Media studies